Postpartum food taboos and dietary intake among Malay women - Kamarudin, Nur Fariehan (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Malay culture believes that during parturition heat is Joss and the women undergo a state of outrageously cold. Malay women comply a 40-day period of resting in accordance with Islamic beliefs. This present study aims to describe the postpartum food taboos and dietary intakes among Malay women, to identify the influential factors in relation to food taboos and dietary pattern, to determine the frequency of fruits and vegetables intake during confinement, and to identify the rationale of practicing the traditional food taboos and dietary intake during confinement. A cross-sectional study was conducted in purposively selected government clinics in Kota Bharu, Kelantan from April to May 2013. A total of 88 Malay mothers of children less than one year old were interviewed. A set of questionnaire was used to obtain information on socioeconomic background, food taboos, and dietary intakes during postpartum period. Majority of the respondents were aged 25 to 29 years old, had secondary education (61.4%), were homemakers (48.9%), and household income between RM 1000 and RM2000 (39.8%). Most respondents restrict their diet for 31 to 40 days. Mother and mother-in-law were the most influential person during the period of postpartum. Most vegetables and fruits were considered "cold" and were prohibited except for mustard. lkan selar was encouraged and must be eaten during postpartum period. There was significant association between age of respondents and sweet potato and seafood restriction V=32.35, d.f.=l5, P<0.006) and (x2=45.l6, d.f.=IO, P<O.OOOI) respectively. Postpartum food taboos and dietary intake were still popular among Malay women in Kelantan. A proper guideline on dietary intake during period of postpartum will help women and their care givers to ensure the information will be utilized and would benefit women and their baby. xi